Pelatih Kebersyukuran untuk Meningkatkan Kualitas Hidup Guru Sekolah Inklusi - Dwiva Aditya Putri; Sukarti Sukarti; Mira A. Rachmawati (Universitas Islam Indonesia, 2016)
The purpose of this study is to improve inclusion teacher's quality of life by delivering gratitude training. There were 16 teacherswho teach at inclusion's elementary school in Yogyakarta, participated inthis study. They had moderate and low score on quality of life's scale. Data were collected with observation, interview, and quality of life's scale. The result showed that there was a significant difference between subjects who received gratitude training and subjects who did not receive gratitude training(F = 8.082, p = 0.002; p < 0.05). Gratitude training was effective to improved inclusion teacher's quality of life. Key words: quality of life, gratitude, inclusion teachers